2019
DOI: 10.1080/17487870.2019.1671192
|View full text |Cite
|
Sign up to set email alerts
|

Addressing public-value failure: remunicipalization as acts of public entrepreneurship

Abstract: All r i gh t s r eser ved. N o p ar t of t hi s p ap er m ay b e r ep r od u ced i n any f or m wi t h ou t p er m i ssi on of t h e aut h or. © An dr ej Chr i st i an Li n d holst 2019 D ep ar t m en t of Polit ical Sci en ce Aalb org Un iver si t y D en mar k P u bli cat ion s in t h e Ser i es sh ould b e ci t ed as:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Contracting back-in is also reported in other countries such as Australia, Canada, China, Denmark, France, Italy, and the United Kingdom (Gradus and Budding, 2020; Hall et al. , 2013; Lindholst, 2019; Wang et al. , 2018; Wollmann, 2018; Young and Macinati, 2012).…”
Section: Overview Of Contracting Back-in Researchmentioning
confidence: 69%
See 1 more Smart Citation
“…Contracting back-in is also reported in other countries such as Australia, Canada, China, Denmark, France, Italy, and the United Kingdom (Gradus and Budding, 2020; Hall et al. , 2013; Lindholst, 2019; Wang et al. , 2018; Wollmann, 2018; Young and Macinati, 2012).…”
Section: Overview Of Contracting Back-in Researchmentioning
confidence: 69%
“…Gradus and Budding (2020) found that contracting back-in became more common than privatization in Dutch municipalities. Contracting back-in is also reported in other countries such as Australia, Canada, China, Denmark, France, Italy, and the United Kingdom (Gradus and Budding, 2020;Hall et al, 2013;Lindholst, 2019;Wang et al, 2018;Wollmann, 2018;Young and Macinati, 2012).…”
Section: Overview Of Contracting Back-in Researchmentioning
confidence: 73%
“…The second half of the 20th century spawned a number of papers on public entrepreneurship [39][40][41], and ever since, the interest on this topic has not waned [42][43][44][45], with the interest in healthcare entrepreneurship specifically also being maintained [7,[46][47][48][49][50].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is expected that PE adoption by public agencies will lead to the maximization of public outputs with fewer resources or inputs (e.g. Ali et al, 2019;Cunningham et al, 2016;Dhliwayo, 2017;Klein et al, 2013;Kouakou, 2018;Lee et al, 2012;Lindholst, 2019;Najmaei & Sadeghinejad, 2016;Xu & Carey, 2015). However, despite the expected efficiency improvements of PE adoption, some countries have been reluctant to embrace PE in their public agencies (Carnes et al, 2019;Liddle, 2016b;Najmaei & Sadeghinejad, 2016).…”
Section: Article Typementioning
confidence: 99%